2019
DOI: 10.9734/cjast/2019/v37i530340
|View full text |Cite
|
Sign up to set email alerts
|

Dilution Ratio and Pasteurization Effects on the Physico-chemical Characteristics of the Pulp of Saba senegalensis of Côte d'Ivoire

Abstract: Aims: The objective of this study was to evaluate the effect of dilution ratio and pasteurization on physico-chemical parameters of Saba senegalensis pulp in the context of its recovery. Study Design: The experimental set-up was of a completely randomized design. Place and Duration of Study: This study was carried out in the Department of Food Science and Technology, at the Laboratory of Food Biochemistry and Tropical Product Technology (BATPTL) of Nangui Abrogoua University, Abidjan, Côte d'Ivoire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
2

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 6 publications
1
3
2
Order By: Relevance
“…This acidity could allow extending the shelf life of fresh fruit and inhibiting the multiplication of pathogenic microorganisms (Mudambi and Rajagopal, 2006). The mean pH of the S. senegalensis pulps from Burkina Faso was closed to those obtained by Kouakoua et al (2019) from Côte d'Ivoire (pH 2.85) and Sarr et al (2018b) from Senegal (pH 2.77). In contrast, Boamponsen et al (2013) reported a lower pH for the pulp harvested in Ghana.…”
Section: Biochemical Composition Of S Senegalensis Pulpsupporting
confidence: 72%
See 4 more Smart Citations
“…This acidity could allow extending the shelf life of fresh fruit and inhibiting the multiplication of pathogenic microorganisms (Mudambi and Rajagopal, 2006). The mean pH of the S. senegalensis pulps from Burkina Faso was closed to those obtained by Kouakoua et al (2019) from Côte d'Ivoire (pH 2.85) and Sarr et al (2018b) from Senegal (pH 2.77). In contrast, Boamponsen et al (2013) reported a lower pH for the pulp harvested in Ghana.…”
Section: Biochemical Composition Of S Senegalensis Pulpsupporting
confidence: 72%
“…In this study, the content of titratable acidity varied from 3.53 ± 0.12% (Hndp) to 5.29 ± 0.49% (Spnp) with an average of 4.48 ± 0.57%. This average is higher than that (2.20%) reported by Kouakoua et al (2019). The fruit being a climacteric fruit, this difference could be explained by ripeness and varietal differences among fruits.…”
Section: Biochemical Composition Of S Senegalensis Pulpcontrasting
confidence: 63%
See 3 more Smart Citations